Investigation of oxygen gain in polymer electrolyte membrane fuel cells - Prasanna, A; Ha, HY; Cho, EA; Hong, SA; Oh, IH (ELSEVIER, 2004)
The polymer electrolyte membrane fuel cell (PEMFC) faces an efficiency loss, so called "oxygen gain", when the cathode gas is changed from oxygen to air due to the reduced oxygen partial pressure. To reduce the oxygen gain of a PEMFC, performance and oxygen gain of the single cells were evaluated as a function of carbon support, Pt content in the catalyst, membrane electrode assembly (MEA) fabrication process and the cathode humidification temperature. Among the tested carbon supports, Black Pearl 2000 and an undisclosed carbon produced the best performance and the lowest oxygen gain with their high surface area and high pore volume. As the Pt content in the catalyst increased from 10 to 60 wt.%, Pt surface area and the electrode thickness decreased leading to decreases in active catalyst surface area, and an ohmic and mass transfer resistance of the electrode. Due to trade-off effects, 20 wt.% Pt exhibited the highest performance. Compared to the conventional MEA, the MEA prepared using catalyst-coated membrane (CCM) method showed better performance with reduced catalyst loss into the gas diffusion media (GDM). As the cathode humidification temperature increased from 55 to 85 degreesC, the amount of water supplied to the cathode increased, leading to an increase in ionic conductivity of the membrane and another probability of water flooding. Thus, in the low current density region, performance of the single cell was improved with cathode humidification temperature, while in the high current density region, the single cell showed the highest performance at the cathode humidification temperature of 65 degreesC with water flooding at 75 and 85 degreesC. (C) 2004 Elsevier BN. All rights reserved.
Keywords: PORE STRUCTURE; PERFORMANCE; HYDROGEN; PEMFC; LAYER